First report of Campoplex difformis (Gmelin, 1790) associated with the parasitoid wasps fauna of Iran - سمیه اله ویسی; M. Hassani; A. Ameri (نامه انجمن حشره‌شناسی ایران, 2021)
A solitary endoparasitoid of the larva of Gelechidae and probabely Scorbipalpa ocellatella Boyd. (beet moth) (Lep.: Gelechidae) in Hamedan province, Iran, Campoplex difformis (Gmelin, 1790), belonging to the subfamily Campopleginae (Hym.: Ichneumonidae), is reported. These wasps are apparently as parasitoid of sugar beet moth.